Program Evaluation Forms and approaches - Owen, John M (Routledge, 2006)
Program Evaluation 3rd edition has the hallmarks of thoroughness, insight and fluency of other editions but brings us up to date with a map of the evaluation territory new travelers will find invaluable.' Professor Murray Saunders, UK and European Evaluation Societies John Owen's Program Evaluation helps practitioners clarify distinctions between what we evaluate, the various motivations for conducting evaluation, and the approaches attendant to each. Timely evaluation examples liberally sprinkled throughout this book make it exceptionally useful and helpful to practitioners. I highly recommend Program Evaluation.' Professor Marvin Alkin, UCLA Graduate School of Education + Information Studies Everyone involved with policy and program development and delivery is being asked to plan more carefully, reflect more critically and justify their decisions. The key to this is evaluation. Program Evaluation offers a conceptual yet straightforward and practical overview of the evaluation process for both beginners and experienced practitioners. It shows evaluators how to identify appropriate forms, approaches and methods, using an original framework. John Owen examines the contributions of evaluation to program provision, and offers proven techniques for involving stakeholders in the planning process and for disseminating the evaluation findings. This third edition has been thoroughly revised to incorporate recent research on evaluation and new examples of good practice. It includes sections of management of evaluation, negotiating evaluation plans, program logic and ex ante evaluation, evidence based practice, performance management and accountability. With international examples from a range of health, education, welfare, community and other settings, Program Evaluation is an essential reference for anyone involved in evaluation in both the public and private sectors.